2012
DOI: 10.1111/j.1365-3083.2012.02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial Examination of Serum IL‐8, IL‐10 and IL‐1Ra Levels is Significant in Neonatal Seizures Induced by Hypoxic–Ischaemic Encephalopathy1

Abstract: We investigated changes in the levels of significant cytokines in relation to neonatal seizures, a pattern of cytokine concentrations serially and the severity of brain insult. The hypoxic–ischaemic encephalopathy‐induced seizure group consisted of 13 patients, and another 15 normal newborns were enrolled as a control group. All of the initial samples were obtained within the first 24 h of admission, and the second samples were obtained between 48 and 72 h in both groups. Only the third samples were taken in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 28 publications
3
27
1
5
Order By: Relevance
“…Moreover, the obvious elevation of IL-8 can be used as a biological marker for the prognosis of early HIE brain injury, which is easy to occur in neonatal convulsion. [30] Quiniou et al [31] confirmed the leading role of IL-1 in hypoxicischemic brain damage as an important proinflammatory cytokine. It is involved in the whole process of the occurrence and development of hypoxic-ischemic brain damage.…”
Section: Relationship Between Hie and Il-18mentioning
confidence: 87%
“…Moreover, the obvious elevation of IL-8 can be used as a biological marker for the prognosis of early HIE brain injury, which is easy to occur in neonatal convulsion. [30] Quiniou et al [31] confirmed the leading role of IL-1 in hypoxicischemic brain damage as an important proinflammatory cytokine. It is involved in the whole process of the occurrence and development of hypoxic-ischemic brain damage.…”
Section: Relationship Between Hie and Il-18mentioning
confidence: 87%
“…Ряд отечественных и зарубежных авторов указывают на существенную роль про-воспалительных цитокинов в развитии перина-тального поражения ЦНС [10,11,15], а также предикторную значимость определения уровня IL-8 для ранней диагностики повреждений го-ловного мозга у новорожденных в течение 72 ча-сов после рождения [14].…”
Section: иммунологические показатели пуповинной кровиunclassified
“…IL-8 increases in the acute phase of injury in neonates with HIE, and the more severe the injury the higher the IL-8 levels (Lv et al, 2015). In a study of 13 neonates with HIE and epilepsy, most inflammatory factors in the serum were decreased after 8-72 h, however, serum IL-8 levels remained high indicating that IL-8 might be an early biomarker for the diagnosis of neonatal HIE with epilepsy (Youn et al, 2012).…”
Section: Inflammation Related Markersmentioning
confidence: 99%